Learn Ncert All Solutions

from a handpicked tutor in LIVE 1-to-1 classes

from a handpicked tutor in LIVE 1-to-1 classes

# Prove the following: cot 4x(sin 5x + sin 3x) = cot x(sin 5x - sin 3x)

**Solution:**

LHS = cot 4x(sin 5x + sin 3x)

= cot 4x [2sin (5x + 3x)/2 cos (5x - 3x)/2]

[Since sin A + sin B = 2sin [(A + B) / 2] cos [(A - B) / 2]

= (cos 4x / sin 4x) [2 sin 4x cos x]

= 2cos 4x cos x

= 2cos 4x cosx × (sin x / sin x)

[multiplied and divided by sin x]

= (cos x / sin x) × [2cos 4x sin x]

= cot x [sin (4x + x) - sin (4x - x)]

[Using product to sum formulas, 2 cos A sin B = sin (A + B) - sin (A - B)]

= cot x(sin 5x - sin 3x)

= RHS

NCERT Solutions Class 11 Maths Chapter 3 Exercise 3.3 Question 15

## Prove the following: cot 4x(sin 5x + sin 3x) = cot x(sin 5x - sin 3x)

**Summary:**

We got, cot 4x(sin 5x + sin 3x) = cot x(sin 5x - sin 3x). Hence Proved

Math worksheets and

visual curriculum

visual curriculum